(untitled) (Archives of Pediatrics of Uruguay, 2022)
Introduction: the creation of neonatal transport systems showed a landmark regarding reduced morbidity and mortality of newborns (NB). The Pan-American Health Organization estimates that 1% of NBs require admission to an Intensive Care Unit. The ideal transport system would be intrauterine; however, many times this is not possible and neonatal transport services are needed. The regionalization of transport services, the training of human resources and the acquisition of materials have improved and therefore the need for transport services has decreased. Objectives: to describe the situation of newborns who required transport services and assess the impact on these services when acquiring materials and skilled human resources. Methodology: descriptive, retrospective and multicenter study, including all newborns who required transport services in 2016-2019. Variables analyzed: number of births, number of transfers, gestational age (GA), age at the time of transfer, birth weight, stabilization time, oxygen therapy and methods, medication received, means of transport and human resources. Results and discussion: 101 neonatal transfers were carried out, 1.5% of all births. Annual variation: 2% of newborns in 2016, 1.6% in 2017, 1.4% in 2018, 1.1% in 2019. Public sector: 63.3%. The mean GA was 33 weeks (25-40), mode 31 weeks. Extreme pre-terms 4.17%, severe pre-terms 37.5%, moderate pre-terms 17.7%, late pre-terms 15.6% and term newborns 25%. The mean birth weight was 2102 grams (710-4160), mode 1440 grams. The mean number of days at the time of transfer was 2.1 (3 hours-26 days). Transport main indications: prematurity 39.6%, other RDS 22.9%, surgical pathology 13.5%, septic shock 10.4%, asphyxia/seizures 8.3%, and heart disease 3%. Treatment during stabilization: Oxygen therapy: 87.1%. Orotracheal intubation and mechanical ventilation assistance 71%, CPAP 9.7%, nasal catheter 6.4%. 58.5% required surfactant, 77.4% antibiotics, 26.6% inotropes, 3.3% prostaglandins, 3.3% aminophylline. The mean stabilization time was 10.5 hours (3-36 hours). Destination: 64.3% Montevideo, 30.6% Tacuarembó, 3% Salto, 1% Canelones and 1% Minas. Means of transport: land 95% and air 5%. Deceased 1%. Available human resources: in 2016, 1 neonatologist and 6 pediatricians. In 2019, 3 neonatologists, 2 post graduated doctors in neonatology, 1 intensivist pediatrician, 9 pediatricians (who were trained in NB stabilization) and an academic supervisor and referent. Simultaneous neonatal stabilization units with continuous training of the nursing staff were created. Conclusions: the main cause of neonatal transport was severe prematurity. With the acquisition of adequate material and trained human resources, a decrease of almost 50% of these transfers was achieved. Regionalization has been rising even though it should be strengthened, especially in newborns weighing less than 1000 grams.